Assessing (a)symmetry in multilingualism: The case of Mano and Kpelle in Guinea. (August 2021) - Khachaturyan, Maria; Konoshenko, Maria
Aims and objectives: The paper studies Kpelle–Mano bilingualism in the broader context of local multilingual repertoires and assesses symmetry in the patterns of language use. Methodology: We combine natural speech sampling with ethnographic observations, interviews, sociolinguistic surveys and elicitation tasks. Data and analysis: The data analyzed includes 88 questionnaire responses, targeted elicitation with 21 individuals, as well as corpus collection and ethnographic observations over the course of fieldwork from 2008 onwards. Findings: Neither Mano nor Kpelle has an overt prestige value. Marriage patterns and economic activity are symmetrical, and both languages can be in certain cases chosen as a means of interethnic communication. However, bilingualism is typically unreciprocated, and the Mano speak Kpelle more often than the other way round. Contact-induced change is almost exclusively unidirectional, with Kpelle influencing Mano. We suggest relative population size as the main explanatory factor. In contrast, both Mano and Kpelle are in an asymmetric relationship with Maninka, which is frequently used by urban Mano and Kpelle speakers. Even if some Maninka claim to speak Kpelle to a certain extent, they rarely use it in real life. Originality: This paper is a report on a previously unstudied multilingual setting. We stress the theoretical and the empirical importance of the patrilect. In addition to its being the defining identity feature, the patrilect is also the main predictor defining the language choice in communication and the volume of the repertoire. Significance: We applied long-term participant observation in various social settings to obtain a fine-grained account of the rules governing language choice, which a typical background questionnaire would overlook. We also sampled natural and elicited speech of L1 and L2 speakers of Mano and Kpelle, a method that yields better results than proficiency tests because it captures interference in grammar, which has far-reaching consequences for contacting languages.